Evolutionary Drivers of Conspicuous Spots in Velvet Ants (Hymenoptera: Dasymutilla) - Lopez, Vinicius Marques; Allen, William L.; Polido, Mariáh; Almeida, Lucas Henrique [UNESP]; Williams, Kevin Andrew; Ferreira, Rhainer Guillermo (Wiley, 2025)
Predation plays an important role in animal evolution by selecting for antipredator adaptations. Antipredator color adaptations include conspicuous spots, which are believed to provide protection by deflecting attacks to harmful or peripheral body parts, deimatic signaling, or as conspicuous warning coloration. The utility of antipredator signals is context-dependent and may be influenced by the environment. In this study, we investigated the selective forces acting on the evolution of conspicuous spots on velvet ants (Mutillidae: Dasymutilla). We tested whether conspicuous spots in 80 species of velvet ants evolved in (i) forest-dwelling species, (ii) habitat-generalist species, or (iii) species predated by diverse birds and frogs. Results show that conspicuous spots are more likely to evolve in forest-dwelling species and in areas with more canopy cover, whereas species inhabiting open areas and deserts tend to lose them. Moreover, taxa with conspicuous spots transition between open and forested habitats less often. Spot presence was not associated with predator diversity. We suggest that spots in velvet ants require complex visual environments to be effective, which may limit their habitat occurrence. In simpler environments, carrying conspicuous spots could be costly due to increased exposure to visual predators.
Keywords: animal coloration; antipredator signaling; closed habitats; habitat complexity